2018
DOI: 10.3390/ijms19071947
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights on Alzheimer’s Disease Originating from Yeast Models

Abstract: In this review article, yeast model-based research advances regarding the role of Amyloid-β (Aβ), Tau and frameshift Ubiquitin UBB+1 in Alzheimer’s disease (AD) are discussed. Despite having limitations with regard to intercellular and cognitive AD aspects, these models have clearly shown their added value as complementary models for the study of the molecular aspects of these proteins, including their interplay with AD-related cellular processes such as mitochondrial dysfunction and altered proteostasis. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 239 publications
0
53
0
Order By: Relevance
“…The intriguing fact that most of the processes of ageing are also conserved in yeast makes it an appropriate model for age-related neurodegenerative diseases. S. cerevisiae cells bud asymmetrically for up to 20-25 cycles, indicating a limited replicative lifespan [16]. The division of cells produces smaller daughter cells and leaves scars on the cell surface [391].…”
Section: Future Perspectives Of Using Yeast As a Model Organism For Amentioning
confidence: 99%
See 1 more Smart Citation
“…The intriguing fact that most of the processes of ageing are also conserved in yeast makes it an appropriate model for age-related neurodegenerative diseases. S. cerevisiae cells bud asymmetrically for up to 20-25 cycles, indicating a limited replicative lifespan [16]. The division of cells produces smaller daughter cells and leaves scars on the cell surface [391].…”
Section: Future Perspectives Of Using Yeast As a Model Organism For Amentioning
confidence: 99%
“…These intracellular cues are also conserved in yeast cells with more than 60% of its genes having human homologs or at least one conserved domain [15]. The major yeast models used for AD studies involve Saccharomyces cerevisiae [16]. These models for AD studies have been very important in understanding the role of conserved fundamental eukaryotic processes in AD pathology to develop methods to find potential therapeutics [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Yeast models Yeast, in particular Saccharomyces cerevisiae, is one of the simplest and most-studied eukaryotic organisms available for the study of cellular pathologies (Verduyckt et al, 2016;Tenreiro et al, 2017;Seynnaeve et al, 2018;Rencus-Lazar et al, 2019). This organism has a short generation time, and an arsenal of research tools is available for its study (Smith and Snyder, 2006).…”
Section: Aβ Modelsmentioning
confidence: 99%
“…Fission yeast is an excellent system to study the complex intracellular mechanisms underlying neurodegenerative diseases such as Alzheimer's disease (AD). Heterologous expression of Tau and Aβ can provide new insights into the pathobiology of these proteins in vivo as well as the screening of compounds that may be useful in treatment and/or prevention of AD [45]. Recently, it was reported that ginger (dietary condiment) fermented with S. pombe had neuroprotective effects on in vivo models of AD.…”
Section: Heterologous Protein Expressionmentioning
confidence: 99%